IMPLEMENTASI READING CHALLENGE BERBASIS JURNAL REFLEKTIF UNTUK MENINGKATKAN LITERASI MEMBACA CERITA SISWA KELAS V SEKOLAH DASAR 15 MATARAM - Nurhayati; Nurhamidah; Nurjohan; Nurkhalifah; Nurfaija; Syafruddin Muhdar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine in depth the implementation of a reflective journal-based reading challenge in an effort to improve story reading literacy in fifth-grade students at Mataram 15 Public Elementary School. The background of this study is based on the low interest and ability of students to read, especially in understanding narrative texts in depth and comprehensively. The research method used is a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects consisted of 18 fifth-grade students who participated in the reading challenge program with the use of reflective journals as a supporting medium in the learning process. The results showed that only 8 students were able to complete the reading as a whole and fill out the reflective journal completely, while the other 10 students were not able to fulfill both aspects optimally. Factors that influenced this achievement include low interest in reading, students' difficulties in developing reflective writing, and the mismatch of the length and complexity of the reading with the students' ability levels. Nevertheless, students who successfully completed the activity showed an increase in reading engagement, understanding of the story content, and critical thinking skills. These findings indicate that the integration of reading challenges and reflective journals has the potential to improve students' reading literacy. However, the effectiveness of its implementation needs to be supported by adaptive learning strategies, intensive mentoring from teachers, and the selection of reading materials that are in line with the characteristics and abilities of study.